Oxygen measurement in the Labrador Sea: profiling oxygen floats as new observation method - Kihm, Christoph (2010)
The aim of this study was to analyze the annual cycle of dissolved oxygen (O2) in the central Labrador Sea on the basis of oxygen data observed by autonomous profiling floats during the period September 2003 and August 2006. The Labrador Sea in one of just a few regions where open-ocean deep winter convecion occurs reaching depths of 2000 m and more. The seasonal and interannual cycles of temperature, salinity, and oxygen are affected by physical and biological factors. The published separation of the seasonal freshwater pulse between March and September into two freshening periods as well as a slight increase of maximum sea surface temperature by 0.3°C to 0.8°C was confirmed. The seasonal oxygen cycle of the mixed layer is highly dynamic varying from moderate undersaturation during late winter to marked supersaturation in spring and early summer. The published climatological picture for oxygen was largely confirmed whereby the smoothing effect of the climatology becomes obvious. The mixed layer depth was determined using an O2 difference criterion of 5 mumol L-1 which seems to be a reasonable threshold for this region. Convective deepening of the mixed layer is associated with a strong increase of the upper ocean O2 inventory which was estimated at 8.3 to 15.1 mol O2 m-2. This inventory increase is correlated with the maximum depth of the winter mixed layer. Hence the increase found during winter 2003/2004 was largest at 15.1 mol O2 m-2. There is indication that the North Atlantic Oscillation (NAO index) affects the deep ventilation in the Labrador Sea as a correlation was found between the NAO index and the winter increase of the deep O2 inventory (710-1350 m) with a time lag of 1 year. Also, an increase of the maximum summer oxygen concentration by 17.4 mumol L-1 in surface waters was observed which is indicative of a stronger or more rapid primary production. The oxygen dataset was also used to estimate the air-sea gas transfer coefficient of oxygen as a function of wind speed. The results in general agree ...